Sojourn maps: A report of departure and return. Issue 1 (1st April 2023) - Gunn, Matt
These maps were drawn on a sandy isthmus known as the Neck on lunawuni / Bruny Island in Tasmania, Australia. This low-lying, tenuous geomorphology is one that both connects and protects, this material and psychological presence is amplified in the context of rapid climate change. The nature of the change, as a break from largely predictable patterns of the Holocene epoch, is not just about destruction of the environment and its biodiversity, it is also about the undermining of sedentary modes of existence. My drawings withdraw from mapping as a utility. Instead, they emphasize mapping as a process of documentation in discovery. Mapping in this way is not about representing the form of place through projection. It is about creating a drawing practice in movement, one that sees the value of uncertainty in the process of learning and development. My maps reconceptualize mapping as a performative production in a condition of departure and return. They frame mapping within an experiential and subjective manner, opening up a reflective and symbolic potential for practices of drawing, architecture and design.